Glycine biosynthesis in rat and sheep muscle - Makkar, H.P.S. (1985)
Glycine is the third most abundant of the amino acids released by muscle. Perfused rat hind-limb and sheep diaphragm preparations were employed to study the origin of glycine produced by non-ruminant and ruminant muscle.